Regulatory Sandbox as a Hybrid Legal Policy Instrument: Recalibrating Legal Certainty and Financial Sector Growth in Indonesia - Sandhi B Permana; Yosua Hia (CV. Norma Global, 2026)
The expansion of financial technology in Indonesia has required regulatory adaptation capable of reconciling innovation with legal certainty and prudential supervision. The regulatory sandbox introduced under OJK Regulation Number 3 of 2024 operates as a structured and time-bound experimentation mechanism embedded within statutory authority under Law Number 21 of 2011 and Law Number 4 of 2023. This article examined the sandbox as a hybrid legal policy instrument and evaluated its implications for legal certainty and financial sector development. Employing a normative juridical approach supported by statutory and conceptual analysis, the study assessed the procedural architecture of the sandbox and incorporated descriptive sectoral data relating to Financial Sector Technology Innovation providers and asset growth. The findings indicated that the sandbox recalibrated legal certainty through codified eligibility standards, sequenced supervisory stages, and defined exit determinations. Empirical developments demonstrated that sandbox institutionalization coincided with increased institutional integration and measurable sectoral expansion, although no direct causal inference was asserted. Governance risks, including supervisory discretion and digital asset volatility, underscored the necessity of transparent administration and sustained consumer protection safeguards. The Indonesian regulatory sandbox therefore reflected a hybrid governance model integrating adaptive flexibility with formal oversight within rule-of-law parameters.